2023
DOI: 10.1002/adfm.202301353
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectric Control of Polarity of the Spin‐polarized Current in Van Der Waals Multiferroic Heterostructures

Abstract: Ferroelectric (FE) control of magnetism at nanoscale, for instance, FE control of the polarity of spin‐polarized current is crucial for technological advances in magnetoelectric and spintronic applications. However, this fascinating functionality has not been reported in nanoscale systems yet. Herein, a new class of FE/A‐type antiferromagnetic heterobilayer/FE van der Waals (vdW) multiferroic structures is found, in which the FE control of polarity of spin‐polarized current is found possible. Take Sc2CO2/CrSiT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 55 publications
(9 reference statements)
0
6
0
Order By: Relevance
“…The strong interlayer magnetoelectric coupling has been successfully established in layered HS multiferroics stacking up atomic layers of ferromagnets and FE materials, which realizes the control of magnetocrystalline anisotropy, magnetic phase transition, Dzyaloshinskii–Moriya interaction, , topological phase, and valley splitting . Particularly, the reversible switching from semiconductor to half-metal in 2D vdW HS based on the FE substrate not only realizes the generation of the spin-polarized carriers but also allows the manipulation, , which opens up the possibility for applications of 2D spintronics devices for memory storage, especially for 2D spin field-effect transistors (sFET). To achieve such device functions, FE materials are expected to always maintain semiconductor properties when they are in contact with ferromagnets.…”
Section: Introductionmentioning
confidence: 99%
“…The strong interlayer magnetoelectric coupling has been successfully established in layered HS multiferroics stacking up atomic layers of ferromagnets and FE materials, which realizes the control of magnetocrystalline anisotropy, magnetic phase transition, Dzyaloshinskii–Moriya interaction, , topological phase, and valley splitting . Particularly, the reversible switching from semiconductor to half-metal in 2D vdW HS based on the FE substrate not only realizes the generation of the spin-polarized carriers but also allows the manipulation, , which opens up the possibility for applications of 2D spintronics devices for memory storage, especially for 2D spin field-effect transistors (sFET). To achieve such device functions, FE materials are expected to always maintain semiconductor properties when they are in contact with ferromagnets.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the variety of 2D intrinsic multiferroic materials is rather rare. Currently, numerous strategies have been proposed to achieve multiferroic materials, including doping FE compounds with magnetic transition metal (TM) ions, composing FM monolayers and FE monolayers to form 2D multiferroic heterostructures, sliding two FM monolayers to achieve electric control of magnetism, , etc. In addition, the intercalation method by intercalating atoms, ions, , or molecules has been determined to be an effective method to modulate the physical properties of 2D layered materials. For example, Tu and Wu found that inserting 3d TM atoms in layered MoS 2 and Bi 2 Se 3 could induce switchable vertical polarization as well as electrically tunable magnetism .…”
Section: Introductionmentioning
confidence: 99%
“…7,19 In particular, the staggered energy band alignment (type II or Zscheme) can significantly inhibit the recombination of photogenerated electron−hole pairs and facilitating electron and hole separation, which is critical to improve photocatalytic efficiency. 20−23 In recent years, various two-dimensional (2D) ferroelectric heterostructures have surged to the forefront of this field because they not only retain the unique characteristics of isolated 2D ferroelectrics material but also show many fascinating physical properties, for example, ferromagnetic− ferroelectric coupling in multiferroic systems, 24,25 ferroelectric Rashba effect induced valley polarization, 26,27 and the ferroelectric quantum spin Hall effect. 28,29 These appealing performances suggest the 2D ferroelectric heterostructure with potential applications ranging from sensors, field-effect transistors (FET), information storage, and optoelectronic devices.…”
mentioning
confidence: 99%
“…In recent years, various two-dimensional (2D) ferroelectric heterostructures have surged to the forefront of this field because they not only retain the unique characteristics of isolated 2D ferroelectrics material but also show many fascinating physical properties, for example, ferromagnetic–ferroelectric coupling in multiferroic systems, , ferroelectric Rashba effect induced valley polarization, , and the ferroelectric quantum spin Hall effect. , These appealing performances suggest the 2D ferroelectric heterostructure with potential applications ranging from sensors, field-effect transistors (FET), information storage, and optoelectronic devices. Nevertheless, the microscopic role of ferroelectric polarization in 2D ferroelectric heterostructures photocatalytically is rarely studied.…”
mentioning
confidence: 99%